Yield and yield attributes of rapeseed mustard (Brassica) genotypes grown under late sown condition (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted at the Central Research Station of BARI, Gazipur for two consecutive years 2010-11 and 2011-12 with 30 varieties/ genotypes of rapeseed-mustard under three dates of sowing viz., 25 November, 5 December, and 15 December to determine changes in crop phenology, growth and yield of mustard genotypes under late sown condition when the crop faced high temperature. Days to flowering and maturity were different at different planting times. Date of sowing significantly influenced plant height, siliquae/plant, seeds/siliqua, seed yield, and oil content of seed in both the years. The highest seed yield (1310 and 1535 kg/ha) was obtained from the first planting (25 November) in both the years, which was significantly different from two other dates of sowing. Yield and yield attributes of different varieties varied significantly. Among the varieties, BARI Sarisha-16 of Brassica juncea gave significantly the highest seed yield (1495 and 1415 kg/ha), which was statistically identical to BJDH-11, BJDH-12, BJDH-05, BJDH-20, and BARI Sarisha-6 and significantly different from all other varieties. Interaction effect of variety and sowing date significantly influenced plant height, number of siliquae per plant, number of seeds per siliqua, seed yield, and strover yield. The highest seed yield (1758 and 1825 kg/ha) were recorded from BJDH-11 and BARI Sarisha-16 of Brassica juncea at 25 November planting and BJDH-11 produced the highest yield at 15 December in both the years. The maximum strover yield (3758 and 3825 kg/ha) were obtained from BJDH-11 and BARI Sarisha-16 of Brassica juncea at 25 November planting during 2010-11 and 2011-12. The highest oil content of seeds (44.4 % and 45.9%) were obtained from the seed of BARI Sarisha-6 and BARI Sarisha-14 at 25 November planting in both the years. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20434 Bangladesh J. Agril. Res. 39(2): 311-336, June 2014